Analysis of Mathematical Problem Solving Ability of Junior High School Students on Relation & Function Material with Polya's Strategy - Erva Erviana; Yunika Lestaria Ningsih; Putri Fitriasari (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2020)
This research aims to describe the mathematical problem solving skills of junior high school students in relationship materials and functions with Polya strategy. The method used in research is a qualitative descriptive method. This research was conducted at SMP Negeri 35 Palembang with a class XI.6 research sample of 30 people. The research subjects were taken by 6 students, who were grouped into three categories, namely high, medium and low who were taken 2 people each from each category.. The data collection techniques in this study are tests, interviews and documentation. The results of the data obtained are then analyzed using data reduction analysis techniques, data presentation and verification. So the results of the study show that: 1) students who have high category problem solving skills are able to carry out all stages of problem solving, 2) students who have problem solving skills category are able to carry out the problem solving stages of the problem, but at the stage of carrying out planning and problem solving students make mistakes in operation and are not able to perform the stage of planning the answer correctly, 3) students who have low category problem solving skills are only able to carry out one stage that is understanding the problem and not being able to carry out the stage of planning the solving strategy planning and troubleshooting and re-examining the answers obtained correctly.